Metode Background Substraction untuk Pencarian Tempat Parkir Menggunakan Kamera Pengawas - Kristian Adi Nugraha (Maranatha University Press, 2020)
Indonesia is a country with the high number of vehicle users. The high number of vehicles affecting the needs of parking area. Meanwhile, wider parking area would make people difficult to find available parking slot. One of the solution is creating smart parking system, a system that can help people to find available parking slot easier. Most of smart parking system using an expensive sensors installed on each parking slot to detect parked car on that slot. However, the installation of that system is too expensive, then not everyone can afford it. This research purpose is to create a cheaper smart parking system using the help of CCTV's camera. System reading the image of parking area from CCTV's camera, then decide all of the captured parking slot are available or not using background substraction method. From the testing result, the accuracy of this smart parking system is 93.69%.